A Novel Approach to Enhancing Upper Extremity Coordination in Children with Autism Spectrum Disorder. Issue 3 (3rd May 2020) - Gamez Corral, Alejandra S.; Manning, Rhonda; Wang, Chaoyi; Cisneros, Ana; Meeuwsen, Harry J.; Boyle, Jason B.
Abstract: Recent studies examining children diagnosed with Autism Spectrum Disorder (ASD) have revealed kinematic markers highlighting deficits in the preparatory and online phases of upper extremity movements. In the following study, 12 children with high functioning ASD were first assessed (pre-test) on 15 trials of a reciprocal upper extremity Fitts Law target task by flexing and extending their right arm in the horizontal plane between two targets as fast and accurately as possible. Following the initial assessment, the children either continued with 30 additional trials of the target task (control) or were asked to track a sine wave template (experimental). All participants were then assessed on 15 trials of the target test (post-test). Results reveal that tracking the sine wave template during training not only produced faster movements compared to the control but also produced these movements in a more harmonic way.